Analysis of Waveform of Partial Discharge in Air Insulation Measured by RC Detector - Michael Stevano Sinurat; Umar Khayam (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
This study discusses the measurement of Partial Discharge (PD) in air insulation. Partial Discharge Measurement is very important to know the condition of electrical equipment. The cause of partial discharge is not only old equipment, but also from set-up errors and insulation problems. In this research partial discharge measurement was performed by using electrical methods. Electrical method use RC Detector. The modeling of partial discharge was done by using needle-plane electrode distant 1 cm in air insulation. Partial discharge measurement parameters include the measurement of Background Noise (BGN), Partial Discharge Inception Voltage (PDIV) and PD Waveform. The Partial Discharge measurement result show that Vpp of BGN ON is higher than Vpp of BGN OFF. The negative PDIV signal first appeared for the RC Detector at a voltage 3.55 KV and Positive PDIV at 4.01 KV. Negative and positive PD waveform for RC Detector at 5 KV, 5.5 KV, 6 KV, 6.5 KV and 7 KV respectively, it has been found that the fall time is greater than the rise time, and peak to peak voltage (Vpp) will be greater when the applied voltage is greater.